Efektivitas Ekstrakulikuler Seni Musik Anak Islami dalam Perkembangan Bahasa Anak Usia 4-5 Tahun di TK Muslimat NU 200 Kureksari - Alda Rahmawati; Ilun Muallifah Thohir (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2025)
This study aims to explore the effectiveness of Islamic children's music extracurricular activities in supporting the language development of children aged 4-5 years at TK Muslimat NU 200 Kureksari. The method used is descriptive qualitative with data collection through observation, interviews with teachers and documentation of extracurricular activities. The results of the study indicate that Islamic children's music activities consisting of religious songs and Islamic prayers are effective in improving children's vocabulary, articulation, and understanding of language concepts. Children who participate in this extracurricular activity show significant improvements in speaking skills, mastery of new vocabulary, and understanding of the meaning of Islamic words used in songs. This study concludes that Islamic music has an important role in the language development of early childhood and can be an effective tool in fun language learning.